Precision Medicine Approach to Develop and Internally Validate Optimal Exercise and Weight‐Loss Treatments for Overweight and Obese Adults With Knee Osteoarthritis: Data From a Single‐Center Randomized Trial. Issue 5 (11th May 2021) - Jiang, Xiaotong; Nelson, Amanda E.; Cleveland, Rebecca J.; Beavers, Daniel P.; Schwartz, Todd A.; Arbeeva, Liubov; Alvarez, Carolina; Callahan, Leigh F.; Messier, Stephen; Loeser, Richard; Kosorok, Michael R.
Abstract : Objective: To apply a precision medicine approach to determine the optimal treatment regime for participants in an exercise (E), dietary weight loss (D), and D + E trial for knee osteoarthritis that would maximize their expected outcomes. Methods: Using data from 343 participants of the Intensive Diet and Exercise for Arthritis (IDEA) trial, we applied 24 machine‐learning models to develop individualized treatment rules on 7 outcomes: Short Form 36 physical component score, weight loss, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain/function/stiffness scores, compressive force, and interleukin‐6 level. The optimal model was selected based on jackknife value function estimates that indicate improvement in the outcomes if future participants follow the estimated decision rule compared to the optimal single, fixed treatment model. Results: Multiple outcome random forest was the optimal model for the WOMAC outcomes. For the other outcomes, list‐based models were optimal. For example, the estimated optimal decision rule for weight loss indicated assigning the D + E intervention to participants with baseline weight not exceeding 109.35 kg and waist circumference above 90.25 cm, and assigning D to all other participants except those with a history of a heart attack. If applied to future participants, the optimal rule for weight loss is estimated to increase average weight loss to 11.2 kg at 18 months, contrasted with 9.8 kg if all participants received D + E ( P = 0.01). Conclusion: The precision medicine models supported the overall findings from IDEA that the D + E intervention was optimal for most participants, but there was evidence that a subgroup of participants would likely benefit more from diet alone for 2 outcomes.